Answer:
(9x10^2)(2x10^10)
= 1.9 x 10^13 (In scientific notation)
Explanation:
Expression to be simplified is given as:
(9x10^2)(2x10^10)
= 9x10^2x2x10^10
= 9x2x10^2x10^10
The base here in the expression is same so the power will add up:
= 18 x 10^(2+10)
= 1.8 x 10^12
Using Scientific notation on the expression, we know that the decimal point must after the first digit so that the number let us say x is such that x > 0 and x < 10. To move decimal one place back, we will multiply it with 10^1:
18 x 10^12
= 1.8 x 10 x 10^12
= 1.8 x 10^(1+12)
= 1.8 x 10^13